Reverse Phase High Performance Liquid Chromatographic Method for the Analysis of Letrozole in Pharmaceutical Dosage Forms - Laha, T. K. (Medknow Publications, 2008)
A rapid and sensitive reverse phase high performance liquid chromatographic method is depicted for the qualitative and quantitative assay of letrozole in pharmaceutical dosage forms. Letrozole was chromatographed on a reverse phase C18 column with a mobile phase consisting of acetonitrile and phosphate buffer (pH 7.8) in the ratio of 70:30 v/v. The mobile phase was pumped at a flow rate of 1 ml/min. Acenaphthene was used as an internal standard and the eluents were monitored at 232 nm. The retention time of the drug was 3.385 min. With this method, linearity was observed in the range of 10-100 μg/ml. The LOD and LOQ were found to be 0.51 μg/ml and 1.52 μg/ml, respectively. The method was found to be applicable for analysis of drug in tablets. The results of the analysis were validated statistically.